KEDUDUKAN KESEPAKATAN DAMAI SETELAH PUTUSAN VERSTEK DALAM PERKARA CERAI GUGAT MENURUT HUKUM ACARA PERDATA (STUDI ANALISIS PERKARA NOMOR 213/Pdt.G/2018/PA.Slk) - M Nursalim Yahya; Khairina Khairina (Institut Agama Islam Negeri Batusangkar, 2022)
The purpose of this study was to analyze the considerations of the Solok Religious Court for ratifying the peace agreement letter from the plaintiffs and defendants in order to end the process against case number 213/Pdt.G/2018/PA.Slk which was decided verstek even though the decision was not yet legally binding and Verzet legal action should be taken by the Religious Court. The type of research in this writing is field research and analyzed descriptively qualitatively. The results in the study are first, the process of making a peace agreement between the parties in case number 213/Pdt.G/2018/PA.Slk is that the parties came to the Solok Religious Court by stating their desire to make things better and not wanting to divorce. Second, the consideration of the Solok Religious Court to accept the peace agreement letter is that the amicable certificates of the plaintiffs and defendants can be accepted on the grounds that the case has not yet been legally binding (BHT so that the defendant does not need to take legal action against verzet by keeping in mind the principles of simple, fast and low cost). Third, the review of the civil procedural law on the peace statement made by the parties is that the peace that occurs outside the trial is binding on the two parties who make peace.